Dietary lysine requirement for optimal growth performance and carcass characteristics of late finishing gilts - Loughmiller, J.A.; Kim, I.H.; Woodworth, J.C.; Smith, J.W.II; Bergstrom, J.R.; Hongtrakul, K.; Nessmith, W.B.; Musser, R.E.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In Exp. 1, increasing dietary lysine from .40% to .70% linearly improved ADG, F/G, 10th rib fat depth, and percentage lean in finishing gilts from 200 to 250 lb. Increasing dietary lysine also tended to improve longissimus muscle area. Results from Exp. 2 indicate no improvement in growth or carcass performance of gilts fed greater than .60% lysine. The combined results of Exp. 1 and 2 indicate that finishing gilts from 200 to 250 lb requires between .60% to .70% (18 to 20 g/d) dietary lysine to maximize both growth performance and carcass characteristics.
Keywords: Swine; Finishing pigs; Lysine; Lean growth